Fiscal Shocks and the Exchange Rate in a Generalized Redux Model. (6th August 2015) - Di Giorgio, Giorgio; Nisticò, Salvatore; Traficante, Guido
Abstract This paper studies how the interaction between the monetary policy regime and the degree of home bias in public consumption affects the exchange‐rate response to fiscal shocks in a generalized version of the Redux model of Obstfeld and Rogoff (1995). We show that the joint presence of home bias in public consumption and endogenous monetary policy overturns the result of the Redux model implying an exchange‐rate appreciation in response to an expansionary fiscal shock.